Vagus Nerve Stimulation Paired With Rehabilitation in the Home Environment for People With Chronic Post-Stroke Upper Limb Deficits: Preliminary Findings. - Patel, Ruchi; Spinelli-Guglielmo, Lisa; Antares, Kathleen A.; Diedrich, Annie; Zera, Sarah M. (Advances in Rehabilitation Science & Practice, 2026)
Background: Implantable vagus nerve stimulation paired with upper limb (UL) rehabilitation (Paired VNS) is an effective therapy for chronic ischemic stroke currently being implemented in outpatient centers. However, issues such as constraints in transportation, mobility, or caregiver availability may decrease access to in-clinic therapy for some individuals. An alternative approach may be a mobile therapy model in which outpatient rehabilitation services are delivered in the individual's home. The VNS-REHAB At-Home study is a single-arm trial aimed at assessing feasibility of therapist-activated Paired VNS in the home (or mobile Paired VNS) by examining protocol compliance, therapist/patient acceptance, and safety. The goal of this report was to present the preliminary findings from the first participant cohorts. Methods: Participants completed up to 36 hours of therapist-activated mobile Paired VNS within 18 weeks. Therapist-led sessions were supplemented with self-activated VNS during UL functional tasks. The primary feasibility endpoint was the proportion of participants who completed at least 24 hours of mobile Paired VNS. Outcomes included total session hours, therapist/participant acceptance, and safety. While this study was not designed to establish definitive treatment effects, UL impairment/activity, and patient-reported measures were assessed at multiple timepoints as secondary exploratory outcomes. Results: Participants (n = 11) completed a median of 37.8 (32.5-42.4) hours of mobile Paired VNS over 13 (8-18) weeks. All participants met the primary endpoint. Overall, participants and therapists were satisfied (n = 8) or very satisfied (n = 14). Fugl-Meyer Assessment-Upper Extremity scores improved by a median of 7 points. All participants reported improvements in measures of UL use, activities of daily living, and/or participation. Adverse events were reported amongst 3 participants, and there were no serious events related to procedure or device use. Conclusions: Preliminary data from the VNS-REHAB At-Home trial demonstrate that mobile Paired VNS was successfully implemented, well-accepted, and safe in the home setting, with observed meaningful UL improvements. These initial findings support the ongoing evaluation of mobile Paired VNS as an accessible alternative to clinic-based delivery. Trial Registration: NCT05691023; https://clinicaltrials.gov/study/NCT05691023